Understanding the Use of Dietary Supplements among Athlete and Non-Athlete University Students: Development and Validation of a Questionnaire - Dalia El Khoury; John J.M. Dwyer; Lindsay Fein; Paula Brauer; Sydney Brennan; Irene Alfaro (MDPI AG, 2019)
Background: The purpose of this study is to develop and test the validity and reliability of a questionnaire to evaluate dietary supplement use based on the Theory of Planned Behaviour (TPB). Methods: The questionnaire has sections on demographics, physical activity, dietary supplements, and cognitive constructs based on the TPB. Three stages are followed. In Stage 1, elicitation interviews are conducted on five varsity athletes, five physically active non-athletes, and five physically inactive University of Guelph (UofG) students. In Stage 2, comments and ratings of the TPB-based statements are gathered from 10 subject matter experts to check for content validity. In Stage 3, Cronbach’s α is calculated to determine the internal consistency of the cognitive constructs by a pilot test on 84 Applied Human Nutrition UofG students. Results: Interviews assisted in the formulation of the cognitive constructs’ statements, including intentions, attitudes, injunctive norms, descriptive norms, and perceived behavioural control. Content validity ensured that these constructs did not overlap. Few statements from the cognitive constructs were omitted based on findings from the reliability test, achieving acceptable Cronbach’s α values across all constructs (≥0.70). Conclusions: This supplement use questionnaire will be used in a future study to investigate the use and determinants of dietary supplements among Canadian athlete and non-athlete UofG students.